Social identity in people with multiple sclerosis: a meta-synthesis of qualitative research - Barker, Alex; das Nair, Roshan; Lincoln, Nadina; Hunt, Nigel (Emerald Group Publishing, 2014)
Purpose – Many aspects of the self are lost as a consequence of having multiple sclerosis (MS). A person's identity can be altered by negative self-concepts, which are associated with poor psychological wellbeing and can lead individuals to reconstruct their sense of self. The Social Identity Model of Identity Change argues that previously established identities form a basis of continued social support, by providing grounding and connectedness to others to facilitate the establishment of new identities. Family support is a salient factor in adjustment to MS and may enable the establishment of new identities. The purpose of this paper is to investigate identity reconstruction following a diagnosis of MS.